Implementation and impact analysis of a clinical pharmacy ambulatory: a two-year experience - Mengato, Daniele; Camuffo, Laura; Todino, Federica; Cordiano, Luisella; Condello, Domenica; Bucciol, Catia; Benini, Franca; Russo, Francesco Paolo; Cipriani, Alberto; Sartori, Stefano; Sarzo, Giacomo; Tessarin, Michele; et al. (Frontiers in Pharmacology, 2025)
IntroductionClinical pharmacy services contribute to safer and more effective medication use, yet remain underdeveloped in several countries, including Italy, due to limited recognition and funding. Local initiatives are essential to demonstrate feasibility and impact.ObjectiveTo describe the 2-year implementation of a Clinical Pharmacy Ambulatory (CPA) in a large Italian tertiary hospital, and to evaluate its contribution to medication management, adherence, and interprofessional collaboration.MethodsThe CPA was established within the Hospital Pharmacy Department of the Azienda Ospedale–Università di Padova. It provided three pharmacist-led services: best possible medication history (BPMH), medication review (MR), and patient education programs (PEPs). Services were delivered on-site and through telepharmacy, integrated into the electronic medical record. Outcomes were assessed using key performance indicators, including service volumes, fulfillment rates, acceptance of recommendations, and adherence measures. A survey of healthcare professionals assessed changes in perception of pharmacists’ role.ResultsOver 2 years, the CPA served more than 2,200 patients. BPMH activity increased by 12%, with fulfillment consistently above 97%. Fifty-one medication reviews generated 670 therapeutic recommendations, with high physician acceptance (over 70%). PEPs enrolled 151 patients, achieving excellent adherence outcomes. Surveys showed improved awareness of the pharmacist’s role and stronger support for their integration into multidisciplinary care.ConclusionThe CPA represents the first structured pharmacist-led ambulatory formally described in Italy. It demonstrates feasibility, clinical relevance, and organizational value in a healthcare system where clinical pharmacy is not yet institutionalized. This model may inform broader adoption of pharmacist-led services in countries where clinical pharmacy remains underdeveloped.